Rooted in Bamboo: Uncovering the Lives of Rinconada's Craft Community and Unlocking Its Global Potential - Gonzales, Ruby Jane S. (Recent Research Advances in Arts and Social Studies Vol. 8, 2024)
For more than 30 years, the bamboo craft business in Rinconada District, Camarines Sur, Philippines, has thrived as a local source of income. Using a researcher-developed questionnaire, this descriptive survey research sheds light on the industry's landscape by profiling its key players: bamboo growers and craft processors. Likewise, the research identified critical issues related to bamboo supply and, thereafter, proposed strategies for improving the industry's current state. The bamboo growers are predominantly middle-aged men with families, with a significant portion having completed elementary education. Their small-scale plantations, typically less than a hectare, yield 100- 500 bamboo poles and focus solely on the "Kawayang tinik" or Bambusa blumeana species. Meanwhile, the bamboo craft processors are mostly experienced artisans operating as sole proprietors for over a decade. Their focus lies in creating utilitarian bamboo crafts. However, they face a critical challenge in securing high-quality raw materials, which directly impacts the quality of their finished products. This highlights a key area requiring attention to ensure the industry's continued success. By implementing key recommendations and potentially seeking collaborations with global organizations and initiatives focused on sustainable bamboo development, the Rinconada District bamboo craft industry can strengthen its position, improve product quality, contribute significantly to the local economy, and align itself with the growing global market for sustainable and eco-friendly products.